ANALYSIS OF CONSUMER PREFERENCES TOWARDS SOY MILK IN SIDODADI VILLAGE, KEJURUAN MUDA DISTRICT, ACEH TAMIANG REGENCY - Dwi Nadila; Eva Wardah; Muhammad Authar; Zuriani Zuriani; Riani Riani (Jurnal Mahasiswa Agribisnis, 2025)
Soy milk is one of the processing products which is the result of soybean extraction. Soy milk has a balanced combination of nutrients, which is almost similar to cow's milk but is free of gluten, cholesterol and lactose. The soy milk in Sidodadi Village consists of 2 types of soy milk businesses, namely Cita Rasa soy milk and Halalan Toyyiban soy milk which have different qualities and tastes. The population in this study was consumers of Cita Rasa and Halalan Toyyiban soy milk, the respondents in this study were 60 respondents. This research aims to determine consumer preferences regarding the combination of soy milk product attribute levels and the level of importance of soy milk product attributes in purchasing decisions for soy milk in Sidodadi Village, Vocational Youth District, Aceh Tamiang Regency. This research method uses a quantitative descriptive method using conjoint analysis. The attributes that consumers consider are brand, flavor variants and texture. The results of this research show that the combination of soy milk attribute levels is consumer preference based on utility value, namely soy milk with the Halalan Toyyiban brand (0.008), original taste (0.328), thick texture (0.02). The attributes most considered when purchasing soy milk products based on relative importance (NPR) are first the attributes of taste (72,982), brand (14,446), and texture (12,571).